Factors Associated with the Implementation of Nursing Process among Nurses in a Government Hospital - Yusof, Suzana; Ismail, Roziawati; Mohamed Nor, Shahila Rosliza; Mohamed Som, Zanirah; Shohor, Norhafizatul Akma; Sham, Fatimah (Healthscope: The Official Research Book of Faculty of Health Sciences, UiTM, 2020)
A nursing process is a scientific approach in the provision of nursing care provided by qualified nurses to all patients. It is used in clinical practice worldwide to deliver quality individualized care to patients. This study aimed to study the practice of the nursing process and the factors associated with the implementation of the nursing process among registered nurses (RN). A cross-sectional study was conducted among 293 RN in Sungai Buloh Hospital using self-administered questionnaires adapted from Abebe (2014). About 98.4% of the nurses implemented the nursing process during their working life. Approximately 92.1% of the RN stated that a major factor associated with the implementation of the nursing process was the support from the hospital administration. The nursing process is primarily implemented among nurses in the hospital. However, ongoing education on the nursing process is still required to ensure this practice will be continuously carried out in order to improve patient care practices.